HUBUNGAN TINGKAT PENDIDIKAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI DI PUSKESMAS NEOMUTI TAHUN 2018 - MARIA NAFRIDA AMPU, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Exclusive breastfeeding is the best investment for children's health and intelligence. ASI is the first, main and best food for babies that is natural, and contains nutrients needed in the process of growth and development of babies.The purpose of this study was to determine the relationship between the level of maternal education and the provision of exclusive breastfeeding to infants in the Noemuti health center in North Central Timor in 2018.The research method uses analytical survey with case control or case and control approaches, using primary data with questionnaires for control data and secondary data from the nutrition profile of the puskesmas for case data. This study was carried out in July-September 2018 at the Noemuti Health Center in North Central Timor District. The population in this study were all mothers who had babies aged 7-12 months who had exclusively breastfed in January-March at the Noemuti Health Center in 2018 totaling 34 cases. The sample of this study was for 34 cases, and for the control of 34 people, the sampling technique for the case was total sampling and for control was simple random sampling. Univariate analysis to determine the frequency distribution of each variable, and bivariate analysis with Chi Square and 95% confidence level (? <0.05).The results of the study were mostly respondents for cases with a level of secondary education (SMA / SMK) (73.5%) and for control mostly with primary education (SD, SMP) (50.0%), and there was a significant relationship between level relationships mother's education with exclusive breastfeeding for babies in Noemuti Health Center, Timor Tengah Utara District in 2018 (p = 0.016). There is a relationship between maternal education level and exclusive breastfeeding for babies in Noemuti Health Center North Central Timor District in 2018. Breast milk is a liquid that contains and fulfills all the nutrients needed for physical growth and development of a child.